MANAJEMEN KASUS PEREMPUAN KORBAN KDRT DI PUSAT PELAYANAN PEREMPUAN DAN ANAK (PPPA) PROVINSI DKI JAKARTA - Mulyaningsih, Mulyaningsih; Ifan, Maykel (Istek Widuri Jakarta, 2024)
This research focuses on the persistent issue of annual violence, particularly in personal settings such as domestic environments in Indonesia, where a majority of victims are women aged 15-49. At the Women and Children's Service Center (PPPA) in Jakarta Province, social workers serving as case managers utilize comprehensive case management methods to provide holistic care for these victims. The study aims to elucidate how these social workers employ stages of case management and fulfill their roles in addressing female victims of domestic violence through a qualitative descriptive approach that incorporates interviews, observations, and documentation for data collection.The findings of the research reveal that the case management process at PPPA Jakarta for female victims of domestic violence encompasses engagement, assessment, planning, intervention, monitoring, evaluation, and termination stages. Social workers in their roles as case managers act as connectors, service coordinators, consultants, counselors, planners, problem solvers, and case documenters. Additionally, they take on roles as educators, facilitators, and administrators. Effective management of these cases has led to positive outcomes for clients, including increased feelings of safety, improved emotional regulation, better decision-making capabilities, enhanced economic independence, and improved social functioning